Émilie Du Châtelet’s Metaphysics in Light of her Concept of ‘a Being’ - Clara Carus (Journal of Modern Philosophy)
The first few chapters of Du Châtelet’s Institutions de Physique outline a metaphysical foundation that focuses on the principles of knowledge and the fundamental concepts of our knowledge of the physical world. While the first wave of contemporary Du Châtelet scholarship in the 1970s and 1980s read Du Châtelet’s metaphysical foundation as a stripped-down version of Leibniz-Wolffian metaphysics, the latest work has argued against this by suggesting that Du Châtelet’s metaphysics is a method for her physics and can stand on its own feet. This latter interpretation, most prominently advanced by Brading, succeeds in putting Du Châtelet’s metaphysical theory into focus rather than seeing it as a flawed commentary on Leibniz and Wolff. However, it subordinates her metaphysical foundations to the aims of the science of physics, wherein the core question is how bodily interaction works. This paper argues that Du Châtelet’s metaphysical foundations are not meant to ground the science of physics alone, and instead are to lay the foundation for all knowledge of the natural world. By analysing her previously mostly overlooked conception of what ‘a being’ is in chapter 3, we will see that Du Châtelet’s metaphysical foundations address how we gain knowledge of a natural world in our everyday experience of natural beings and thus come to know ‘beings’ in the first place, i.e. prior to scientific judgements on them. The present paper thus asserts that Du Châtelet’s metaphysical foundations are more than a method for her physics.